2017
DOI: 10.1177/0022034517715432
|View full text |Cite
|
Sign up to set email alerts
|

Association of NOD2 Mutations with Aggressive Periodontitis

Abstract: Aggressive periodontitis (AgP) is characterized by rapid alveolar bone destruction and tooth loss early in life, and its etiology remains unclear. To explore the genetic risk factors of AgP, we performed genome-wide single-nucleotide polymorphism genotyping for identity-by-descent mapping and identified 32 distinct candidate loci, followed by whole exome sequencing with 2 pedigrees of AgP consisting of 3 cases and 1 control in 1 family and 2 sibling cases in the other. After variant filtering procedures and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Other notable investigations have used genotyping arrays with exome content, whole‐exome sequencing, RNA expression/multi‐omics profiling, and several post hoc bioinformatics and machine learning classification approaches to study the molecular and genomic basis of periodontitis. The study of gene expression and other more functional approaches (as opposed to genetic association studies) is a key complement to genome‐wide association studies.…”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 99%
See 1 more Smart Citation
“…Other notable investigations have used genotyping arrays with exome content, whole‐exome sequencing, RNA expression/multi‐omics profiling, and several post hoc bioinformatics and machine learning classification approaches to study the molecular and genomic basis of periodontitis. The study of gene expression and other more functional approaches (as opposed to genetic association studies) is a key complement to genome‐wide association studies.…”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 99%
“…In a recent report, Kitagaki and colleagues used whole‐exome sequencing to identify GPR126 (lead marker: rs536714306) as a candidate genetic risk factor for aggressive periodontitis in a Japanese population. In another recent investigation, Sudo and colleagues used a two‐step approach in a family based study and used whole‐exome sequencing to identify novel mutations in the NOD2 gene, which is also associated with aggressive periodontitis.…”
Section: Genomics Of Traditional Clinical Definitions Of Oral and Denmentioning
confidence: 99%
“…NOD2 SNP rs571102620 was identified as a common genetic variant in the first family and SNP rs104895427 was identified as a common genetic variant in the second family. Target exon sequencing in NOD2 was then performed using 94 genetically unrelated Japanese AgP patients and NOD2 SNPs, rs199858111 and rs765857594, and p.Ala868Thr, were absent or very (MAF ≤0.001) in this Asian population . However, this study only reported a heterozygous rare mutation, which was found in only two families with periodontitis.…”
Section: Identification Of Genetic Risk Factors For Agp Through Identmentioning
confidence: 82%
“…More specifically, in patients with chronic periodontal conditions four genes (NIN, ABHD12B, WHAMM, and AP32) have been identified (Rhodin et al, 2014). Sanger sequencing revealed the association of NOD2 mutations in a Japanese population with aggressive periodontal disease (Sudo et al, 2017).…”
Section: Regulation Of Bone Destruction Ictpmentioning
confidence: 99%
“…The complementary advances in information technology and sequencing devices in this decade have enabled analysis of vast amounts of Omics information, contributing to better understanding of disease activity to improve our prediction for disease onset and progression (Eicher et al, 2020). In recent years, various investigations were carried out using preclinical animal and translational Omics analyses to elucidate pathological mechanisms (Rhodin et al, 2014;Offenbacher et al, 2016;Sawle et al, 2016;Sudo et al, 2017;Maekawa et al, 2019;Shin et al, 2019). Since Omics probe different cellular layers, they are categorized at DNA, RNA, protein, or metabolite levels (Yugi et al, 2016).…”
Section: Diagnostic Devices Salivary Proteome and Salivary Genomementioning
confidence: 99%